Adverse childhood experiences and adult cardiometabolic risk factors and disease outcomes: Cross-sectional, populationbased study of adults in rural Uganda - Wooyoung Kim, Andrew; Kakuhikire, Bernard; Baguma, Charles; North, Crystal M.; Satinsky, Emily N.; Perkins, Jessica M.; Ayebare, Patience; Kiconco, Allen; Namara, Elizabeth B.; Bangsberg, David R.; Siedner, Mark J. (Journal of global health, 2021)
Cardiovascular diseases (CVD) pose a major threat to public health in sub-Saharan African communities, where the burden of these classes of illnesses is expected to double by 2030. Growing research suggests that past developmental experiences and early life conditions may also elevate CVD risk throughout the life course. Greater childhood stress and adversity are consistently associated with a range of adult CVDs and associated risk factors, yet little research exists on the long-term effects of early life stress on adult physical health outcomes, especially CVD risk, in sub-Saharan African contexts. This study aims to evaluate the associations between adverse childhood experiences and adult cardiometabolic risk factors and health outcomes in a population-based study of adults living in Mbarara, a rural region of southwestern Uganda.
Keywords: Childhood experiences; Adult cardiometabolic; Disease outcomes; Population; Rural Uganda